Effective Ion Mobility and Long‐Term Dark Current of Metal Halide Perovskites with Different Crystallinities and Compositions - García-Batlle, Marisé; Deumel, Sarah; Huerdler, Judith E.; Tedde, Sandro F.; Almora, Osbel; Garcia-Belmonte, Germà (Advanced photonics research, 2022)
Ion transport properties in metal halide perovskite still constitute a subject of intense research because of the evident connection between mobile defects and device performance and operation degradation. In the case of X‐ray detectors, dark current level and instability are regarded to be connected to the ion migration upon bias application. Two compositions (MAPbBr3 and MAPbI3) and structures (single‐ and microcrystalline) are checked by the analysis of long‐term dark current evolution. Electronic current increases with time before reaching a steady‐state value within a response time (from 104 down to 10 s) that strongly depends on the applied bias. A coupling between electronic transport and ion kinetics exists that ultimately establishes the time scale of electronic current. Effective ion mobility μi is extracted for a range of applied electric field ξ. While ion mobility results field‐independent in the case of MAPbI3, a clear field enhancement is observed for MAPbBr3 (∂μi/∂ξ>0), irrespective of the crystallinity. Both perovskite compounds present effective ion mobility in the range of μi ≈ 10−7–10−6 cm−2 V−1 s−1, in accordance with previous analyses. The ξ‐dependence of the ion mobility is related to the lower ionic concentration of the bromide compound. Slower migrating defect drift is suppressed in the case of MAPbBr3, in opposition to that observed here for MAPbI3. Perovskite‐based radiation detectors exhibit too large and unstable dark current upon long‐term biasing. A coupling exists between electronic transport and mobile ion kinetics that establishes the time scale of electronic dark current, which slowly increases with time before reaching a steady‐state value. Ionic drift mobility is calculated through ion time‐of‐flight at different applied biases.